Multiple mortality events in bats: a global review. (18th January 2016) - O'Shea, Thomas J.; Cryan, Paul M.; Hayman, David T.S.; Plowright, Raina K.; Streicker, Daniel G.
Abstract: Despite conservation concerns for many species of bats, factors causing mortality in bats have not been reviewed since 1970. Here, we review and qualitatively describe trends in the occurrence and apparent causes of multiple mortality events (MMEs) in bats around the world. We compiled a database of MMEs, defined as cases in which ≥ 10 dead bats were counted or estimated at a specific location within a maximum timescale of a year, and more typically within a few days or a season. We tabulated 1180 MMEs within nine categories. Prior to 2000, intentional killing by humans caused the greatest proportion of MMEs in bats. In North America and Europe, people typically killed bats because they were perceived as nuisances. Intentional killing occurred in South America for vampire bat control, in Asia and Australia for fruit depredation control, and in Africa and Asia for human food. Biotic factors, accidents, and natural abiotic factors were also important historically. Chemical contaminants were confirmed causes of MMEs in North America, Europe, and in islands. Viral and bacterial diseases ranked low as causes of MMEs in bats. Two factors led to a major shift in causes of MMEs in bats at around 2000: the global increase of industrial wind‐power facilities and the outbreak of white‐nose syndrome in North America. Collisions with wind turbines and white‐nose syndrome are now the leading causes of reported MMEs in bats. Collectively, over half of all reported MMEs were of anthropogenic origin. The documented occurrence of MMEs in bats due to abiotic factors such as intense storms, flooding, heat waves, and drought is likely to increase in the future with climate change. Coupled with the chronic threats of roosting and foraging habitat loss, increasing mortality through MMEs is unlikely to be compensated for, given the need for high survival in the dynamics of bat populations.